Case of epidermolysis bullosa acquisita with concomitant anti‐laminin‐332 antibodies. Issue 4 (4th December 2017) - Nishida, Emi; Nishio, Eiichi; Murashima, Hiroko; Ishii, Norito; Hashimoto, Takashi; Morita, Akimichi
Abstract: Subepidermal autoimmune blistering disease including bullous pemphigoid, pemphigoid gestationis, mucous membrane pemphigoid, anti‐laminin‐γ1 pemphigoid, linear immunoglobulin A bullous disease and epidermolysis bullosa acquisita (EBA), are all characterized by direct immunofluorescence microscopy or immunoglobulin deposition on the basement membrane zone. Among them, EBA is a rare acquired subepidermal autoimmune blistering disease of the skin and mucous membranes reactive with type VII collagen, a major component of the epidermal basement membrane zone. Anti‐laminin‐332‐type mucous membrane pemphigoid has pathogenic autoantibodies against laminin‐332, which is a basement membrane heterotrimeric protein composed of α3, β3 and γ2 laminin chains. We describe a 73‐year‐old Japanese man presenting with multiple, annular, tense blisters on the lower legs and oral lesions. Despite the severe clinical manifestations, the disease was successfully controlled by combination therapy of oral prednisolone and mizoribine. This case was confirmed to have autoantibodies to both type VII collagen and laminin‐332 α3 chain by indirect immunofluorescence of 1 mol NaCl‐split normal human skin, various immunoblot analyses and enzyme‐linked immunosorbent assays. This case was a rare case of EBA with concomitant anti‐laminin‐332 antibodies.